Between equal rights : a Marxist theory of international law - Miéville, China (Historical materialism book series, 2005)
This book draws on Pashukanis, critical legal studies and the history of international regulation to critique existing theories of international law. It constructs an alternative Marxist approach, and argues that imperialism is intrinsic to international law.